PENGARUH TOTAL QUALITY MANAGEMENT (TQM), PERILAKU PRODUKTIF KARYAWAN, DAN SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL - Putu Purnama Dewi; Ni Made Kintan Widyaswari; Ayu Rahmaditha Apsari (Faculty of Economics and Business, Universitas Warmadewa, 2025)
Thil s rel sel arch ail ms to ul ndel rstand thel il nflul el ncel of total qul alil ty managel mel nt, produl ctil vel el mployel el bel havil or, partil al or sil mul ltanel oul s rel ward systel ms on managel ril al pel rformancel . Thel samplel for thil s rel sel arch il s all thel fil nancel and accoul ntil ng staff of a fast boat company il n Del npasar Cil ty, totalil ng 100 pel oplel . Data analysil s tel chnil qul el s ul sel Valil dil ty Tel st, Rel lil abil lil ty Tel st, Classil cal Assul mptil on Tel st, Mul ltil plel Lil nel ar Rel grel ssil on Analysil s, Coel ffil cil el nt of Del tel rmil natil on Tel st, F Tel st and t Tel st. Throul gh thel sel fil ndil ngs, il t was foul nd that total qul alil ty managel mel nt had a sil gnil fil cant posil til vel il mpact on managel ril al pel rformancel , el mployel el produl ctil vel bel havil or had a posil til vel and sil gnil fil cant il mpact on managel ril al pel rformancel , thel rel ward systel m had a sil gnil fil cant posil til vel il mpact on managel ril al pel rformancel and total qul alil ty managel mel nt, el mployel el produl ctil vel bel havil or and thel rel ward systel m had a posil til vel and sil gnil fil cant il mpact on managerial pel rformancel .